Factors Mediating School Safety in Charter Schools: An Analysis of Five Waves of Nationally Representative Data. Issue 3 (3rd July 2021) - Hamlin, Daniel; Li, Angran
ABSTRACT: Safety-seeking has fueled the growth of charter schools. Descriptive evidence suggests different possible factors underlying safety in charter schools. This study investigates characteristics mediating the relationship between safety and charter schools by linking five waves of the School Survey on Crime and Safety (SSOCS: 2003–04; 2005–06; 2007–08; 2009–10; 2015–16) to Common Core Data. Analyses of 12, 698 schools indicate that charter schools report fewer incidents of school crime and violence and school disruptions than public schools do. Additionally, small school size, school-based parent volunteering, and less use of disciplinary and student removal practices were the strongest mediators of the relationship between charter schools and safety. Future research is needed to understand the relative contribution of self-selection processes and school strategies to safety in charter schools.